ANALISIS KINERJA PEGAWAI NEGERI SIPIL PADA BIDANG PERHUBUNGAN DARAT DINAS PERHUBUNGAN PROVINSI RIAU - NICANDER RIVALDO; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Riau Provincial Transport Department is implementing elements of the regional government of Riau province to carry out the task of local government based on the principle of regional autonomy and duty auxiliary transportation sector.Employee performance and the factors that influence it is still a common concern because it has a very important role in the system. This study was aimed to identify and analyze the factors that influence the performance along with the civil servants at the Department of Transportation Land Transportation Riau Province.The research was conducted in the transportation department Riau Province. Data sources of primary data (Ability, Motivation and Opportunity). While the secondary data obtained from the personnel associated with the employment data. Data on the observation, study documentation and interviews were tabulated and analyzed qualitatively.The results showed that the ability of the (ability), motivation and opportunity (Opportunity) greatly affects the performance of existing employees. To see the effectiveness of employee performance, indicators of the implementation of duties and functions of employees showed that most of the basic tasks that there has not been performing well.The conclusion from this study is that the main tasks to be indicators of employee performance show has not done well. Therefore, the performance of employees stated that there has not been maximized. Therefore, it is necessary to study the workload contained in the duties and functions as well as advanced aspects of ability, motivation and opportunity employee.Keyword : Performance, employees, productivity.